Dynamics of bioelements during leaf decomposition in three forest ecosystems of semiarid climate in the Duero Basin - Hernández, M I; Santa Regina, I; Gallardo, J F (Arid Soil Research and Rehabilitation, 1995)
The dynamics of bioelements lost during leaf litter decomposition were experimentally determined in three forest ecosystems located in a semiarid zone of the Duero Basin, Province of Zamora, Spain, during 2 years. The three ecosystems were a climax Quercus rotundifolia (evergreen oak) woodland, a paraclimax Pinus pinea (stone pine) forest, and a disclimax P. pinaster (maritime pine) forest. The total content of bioelements found in the litter was low in relation to other forest ecosystems: 27, 14, and 8 kg N ha?1 in Q. pyrenaica, P. pinea, and P. pinaster, respectively; 17, 10, and 9 kg Ca ha?1, respectively; about 2 kg P ha?1, 4 kg K ha?1, and 5 kg Mg ha?1 in the three forests. The Q. rotundifolia woodland potentially returns a greater amount of N and Ca than both Pinus forests. An in situ litter bag method was used for the determination of dynamics of the decomposing leaves. A progressive loss of C, P, and Mg in the decomposing oak leaves and pine needles, and a sharp loss of K were observed; by comparison, a tendency to maintain N and Ca was seen. Pinus pinaster forest had the lowest annual N and P return.
doi: 10.1080/15324989509385911
Keywords: biogeochemical cycles; litter decomposition; pine forests; Quercus rotundifolia; semiarid forests